Social judgment and approval of African immigrants in France by their peers : the role of acculturation strategies and normative and non-normative collective actions - (:unkn) unknown (My University, 2024)
In this PhD thesis, we are interested in social judgment and social approval among African immigrants in France, and the types of normative (i.e., peaceful) or non-normative (i.e., violent) collective actions that they can support to improve their conditions. We analyzed the impact of the acculturation strategies adopted by immigrants on their interactions with their counterparts of the same origin. Indeed, previous research has already shown that the acculturation strategies adopted by immigrants influence the attitudes of members of the host society towards them (Nugier et al., 2016). However, few studies have examined the impact of these factors on relationships among immigrants themselves (Badea et al., 2011). Our studies focused on immigrants from Madagascar (N = 111) and North Africa (N = 106) according to their preference to adopt only the French culture (assimilation) or to preserve only the culture of origin (separation). In accordance with our hypothesis based on the behavioral regulation model of Ellemers (2017), we observed that when an immigrant chooses separation, his peers consider him more moral than competent or sociable, morality thus occupying primacy over all other dimensions. The congruence effect on morality was more pronounced among participants who preferred assimilation and assessed a target with the same preference. These results were also observed in non-immigrants (N = 266) living in Burkina Faso who assessed their Burkinabe immigrant peers in France. Regarding the approval of an immigrant peer, the results confirmed our hypothesis. Immigrants and non-immigrants generally supported their counterparts who had chosen separation over those who had preferred assimilation. This support was stronger when there was congruence between the participant’s strong preference for separation and the target’s preference for the same strategy. The study on the collective behavior of protest among Muslim immigrants from North Africa (N =
Keywords: African Research